Maritime Trade of the Malabar Coast and the Portuguese in the Sixteenth Century - Mathew, K. S. (Brill | Manohar Publishers & Distributors, 2016)
This volume provides a thorough investigation into the dynamics of the maritime trade conducted on the Malabar Coast and the role of the Portuguese in it. It brings out several hitherto lesser known details about the part played by the Indian as well as foreign merchants. The Portuguese, in fact, depended on the merchant financiers of Germany and Italy besides the Flemish traders right from the inception of their maritime enterprise in the Orient. Copper in large quantity was imported into the Malabar Coast from various parts of Europe as part payment for the purchase of pepper and other spices from south western coast of India and for minting of coins. Initially for a quarter of a century the Marakkar merchants worked as collaborators of the Portuguese on the Malabar Coast. When the interest of the Marakkars was overlooked by the Portuguese in favour of the Portuguese settlers, the former turned against the latter. Though the Portuguese did not permit anybody else to deal in spices and other goods declared as monopoly items for three quarters of a century, they had to negotiate written contracts with the foreign merchant firms to bring cash and commodities to the Malabar Coast for direct purchases and for delivering the cargo at the India House in Lisbon against the stipulated price on the basis of these contracts. Unlike the English, the Dutch, the Danes and the French, the Portuguese conducted their trade in the name of the king.